PENGEMBANGAN KOMIK KEANEKARAGAMAN HAYATI SEBAGAI MEDIA PEMBELAJARAN BAGI SISWA SMA KELAS X - Oktaviane Maxtuti, Inge (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
The process of learning requires the media to helpin understanding the concept of material. As consequence,variety of media are needed to make joyfull learning. Thiswas development research of comic of Biodiversity as amedia of learning in class X Senior High School. Thisresearch conducted based on ASSURE model. Theinstrument of this research was validation sheet of comic.The result showed that the theoritical feasibility of comic ofbiodiversity was 98.3%.Keywords: media, comic, biodiversity